1988
DOI: 10.1056/nejm198808183190704
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Respiratory Papillomatosis with Human Leukocyte Interferon

Abstract: Recurrent respiratory papillomatosis is a relentless disease of viral origin in which squamous papillomas frequently obstruct the respiratory tract of children and young adults. No therapy has been proved to be curative for this process. Recent reports have suggested that interferon may cure or dramatically control airway papillomatosis. We evaluated the efficacy of human leukocyte interferon in the treatment of respiratory papillomatosis. One hundred twenty-three patients were randomly assigned to receive tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
83
1
5

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(91 citation statements)
references
References 14 publications
2
83
1
5
Order By: Relevance
“…A recent study revealed the maximal effectiveness of INF-α therapy in patients having RRP with HPV 6 as compared to HPV 11 12 . In addition, these results suggest that long-term IFN-α therapy (mean 32.4±21.6 months) 12 was more effective in preventing relapse than the a short course (0.5 or 1 year) 13,15 of injection. Accumulation of additional evidence, however, is required to determine the dosage and duration of IFN-α treatment suitable for patients with RRP.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A recent study revealed the maximal effectiveness of INF-α therapy in patients having RRP with HPV 6 as compared to HPV 11 12 . In addition, these results suggest that long-term IFN-α therapy (mean 32.4±21.6 months) 12 was more effective in preventing relapse than the a short course (0.5 or 1 year) 13,15 of injection. Accumulation of additional evidence, however, is required to determine the dosage and duration of IFN-α treatment suitable for patients with RRP.…”
Section: Discussionmentioning
confidence: 77%
“…Since the early 1980s, interferon has been used as an adjuvant agent in treating patients with RRP and is the most extensively investigated of these agents. However, debate is ongoing regarding the effectiveness of long-term IFN-α therapy, with even multicenter studies on the application of IFN-α as an adjuvant for RRP therapy providing contradictory results 13,15 . A recent study revealed the maximal effectiveness of INF-α therapy in patients having RRP with HPV 6 as compared to HPV 11 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-interferon is an immunomodulatory cytokine with antiviral and antiproliferative properties and was the first widely used adjuvant drug for treating RRP, with diverse results ranging from better prognosis to absence of response. 6,9 The evidence has failed to support its use, since the reports have mostly been based on case reports and clinical trials have shown varied results with limited follow-up. 6,9,10 The association between interferon and polyethylene glycol, which is called pegylated interferon, increases the half-life of the drug, eliminates immunogenicity and improves the pharmacokinetics of the protein, such that it can be administered once a week.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in the 1988 article Treatment of recurrent respiratory papillomatosis with human leukocyte interferon. Results of a multicenter randomized clinical trial [26].…”
mentioning
confidence: 99%